Molecular and Clinical Characteristics of Primary Pulmonary Lymphoepithelioma-Like Carcinoma - Fan, Ying; Shan, Qianyun; Gong, Jiali; Qin, Jing; Lu, Hongyang (Frontiers in Molecular Biosciences, 2021)
Objectives Primary pulmonary lymphoepithelioma-like carcinoma (PPLELC) is an extremely rare subtype of non-small cell lung cancer (NSCLC). Currently, there are no established treatment protocols due to rarity of the cancer. Thus, this study aimed to explore the molecular and clinical characteristics of PPLELC. Study design and setting Data from patients with PPLELC who were admitted to Zhejiang Cancer Hospital from August 2009 to September 2020 were retrospectively collected. Next-generation sequencing was performed to obtain a genomic profile and tumor mutation burden (TMB) value of patients with adequate tissue and divided them into 2 groups according to the expression level of PD-L1. The correlation of PD-L1 expression and the clinicopathological characteristics was evaluated by Pearson Chi-square test. Kaplan-Meier curves was applied to present the probability of survival between PD-L1 expression level and overall survival (OS). Moreover, the literature on the immunotherapy of advanced PPLELC published in PubMed between 2016 and 2020 were reviewed and the efficacy of immunotherapy were analyzed. Results A total of 18 patients pathologically diagnosed as PPLELC were included. After a follow-up period of 8.8 to 138 months, 14 patients survived, 3 patients died and 1 patient lost, the median OS was 45.3 months. 7 samples (tissue-available) tested by NGS and the median TMB was 2.5 mutations/Mb. 19 somatic mutated genes were recognized and TP53 (43%) and CYLD (43%) were the two most commonly mutated genes. Only 7 patients who underwent NGS were tested for PD-L1. 3 patients with high PD-L1 expression (PD-L1≥ 50%) and 4 patients with low PD-L1 expression (PD-L1 <50%) were included. No significant correlation was observed between PD-L1 expression and clinical characteristics(P > 0.05) and OS (P =1). What’s more, 11 PPLELC received immunotherapy were collected. 4/11 (36.4%) patients achieved PR, 6/11 (54.5%) patients achieved SD, and 1/11 (9.1%) patients achieved PD and the disease control rate (DCR) was 90.9%. Conclusions The prognosis of PPLELC is better than that of other NSCLC, and immunotherapy may be a promising treatment to prolong the survival of advanced PPLELC patients. Whether the immunotherapy efficacy of PPLELC can be predicted by PD-L1 and TMB needs further clinical investigation.